SENSITIVITY OF BAY LEAF (Syzygium polyantha) SOLUTION TOWARD Aeromonas hydrophila - Vekri Ramadhi; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted from Juni to October 2018, atParasites and Fish Disease Laboratory, Faculty of Fisheries and Marine, University of Riau. The Purpose of this study was to determine the sensitivity of bay leaf (Syzygium polyantha) solution as antimicrobial to Aeromonas hydrophila, the range of Minimal Inhibitory Concentration (MIC) and the lethal dose (LD50) bay leaf (Syzygium polyantha) solution against to catfish (Clarias sp.) (8-10 cm) by immersion for 24 hours. Sensitivity test is using the method of Kirby-Bauer disk blank 6 mm disc with dose used were 100%, 90%, 80% , 70%, 60%, 50%, 40%, 30%, 20%, 10%,9%, 8%, 7% and control Novobiocin. The result shown that the bay leaf solution can inhibit the growth of bacteria Aeromonas hydrophila that in the dose of 7% with 6,13 mm clear zone . MIC test showed this resueld is 12% has a number of colonies of bacteria aqual 159.66 CFU/mL  is able to inhibit the growth of bacteria Aeromonas hydrophila. Dose LD50 bay leaf solution against catfish by immersion for 24 hours in 13,5% .Keywords: Bay leaf, Sensitivity, Minimum Inhibitory Concentration, Aeromonas hydrophila,  LD50.